Influence of Socioeconomic and Working Status of the Parents on the Incidence of their Children’s Dental Caries - Niha Naveed1 , Kishorekumar S2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dental caries, or tooth decay, is an infectious process involving breakdown of the tooth enamel.Children aresusceptible to caries as soon as the first teeth appear, which usually occurs around age 6 months.It is knownthat socioeconomic status affects the health-related quality of life of children.Family income, occupationalstatus, and educational achievement are socio-economic status indicators that have been found to affect thelife opportunities of an individual.